Cyclist' safety perceptions of cycling infrastructure at un-signalised intersections: Cross-sectional survey of Queensland cyclists. (September 2017) - Ng, Athena; Debnath, Ashim Kumar; Heesch, Kristiann C.
Abstract: Previous research suggests that cyclists' perceptions of the safety of cycling infrastructure influences their desire to ride on that infrastructure. Cycling infrastructure includes both cycling facilities and cycling-supportive road treatments. While researchers have previously examined the safety perceptions of cycling infrastructure on midblock road sections, little is known about the safety perceptions of cycling infrastructure at intersections. The aim of this study was to investigate which types of cycling infrastructure do cyclists perceive to be the safest at un-signalised intersections. This study was conducted in Queensland, Australia. Adult members of bicycle organisations (N=214) completed an online survey about their demographic characteristics, cycling habits, previous near-miss or collision experiences while cycling, and safety perceptions of cycling infrastructure at intersections. General linear mixed-modelling was used to examine associations between safety perceptions and 12 types of cycling infrastructure at three different motorist-cyclist interaction scenarios. Off-road bicycle paths and footpaths were perceived to be the safest cycling infrastructure at un-signalised intersections ( p <0.05). While cycling through an intersection, participants were more concerned about being sideswiped than being struck directly at the side by a motorist ( p <0.05). The findings suggest that cyclists' safety perceptions of cycling infrastructure at un-signalised intersections are associated with motorists' yielding behaviour towards cyclists. Cyclists felt safer using cycling infrastructure where they had to give way to turning motorists at the intersection than using cycling infrastructure where they had the right of way. By doing so, cyclists can decide whether or not it is safe to cross the intersection rather than worry about turning motorists who could be attempting to outrace them. In practice, assessing motorists' behaviours and attitudes towards cyclists should be considered before designing and implementing cycling infrastructure at intersections. Highlights: Safety perceptions of cycling infrastructure at intersections was researched. Off-road bicycle paths was perceived to be the safest cycling infrastructure. Cyclists were more concerned about being sideswiped than taking a direct hit at the side.